GENDER WAYANG: FROM RITUAL INTO SECULER - Suharta, I Wayan (International Conference on Cultural Studies, 2018)
Gender Wayang is one of the most important set of ensemble in Bali. It is not only aimed for accompanying a certain Shadow Puppet performance, but also it remain possesses a portion and function in almost every religiously ritual activity as a complement of spiritual needs. The presentation of Gender Wayang is a prominent key element which is conditioned into social activities, and it is considered to be able to support the necessity of the society for both morraly and spiritually. Gender Wayang from ritual into seculer is an expression of the artists to express their creative idea which posses a meaningful significance for the arts world and positively responsed by the peoples all over the world. This key analysis is a dinamic idealization of the peoples of Bali for the sake of aesthetical values appreciation and developement. The concerned problem to be analized is the developement of Gender Wayang’s function and creativity,, it is one of the various fenomenons of karawitan in the framework of developement of Balinese performing arts. The dessemination of Gender Wayang’s roles from ritual into seculer is caused by the demand and the nessesaty of it peoples, in order to anticipate the developement of time/era and value assesment. Gender Wayang is a masterpiece of the arts of which endeavors to enhance and dinamize the traditional values with the demand capasity developemnt. Gender Wayang becomes a seculer performance because of its art creativities those are fibrating an artistic dimenssion of which can still be recognized and appreciated by the peoples of Bali.